2022
DOI: 10.1186/s12891-022-05936-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary hip and knee arthroplasty at district level is safe and may reduce the burden on tertiary care in a low-income setting

Abstract: Background Arthroplasty procedures in low-income countries are mostly performed at tertiary centers, with waiting lists exceeding 12 to 24 months. Recently, this is further exacerbated by the impact of the Covid Pandemic on elective surgeries. Providing arthroplasty services at other levels of healthcare aims to offset this burden, however there is a marked paucity of literature regarding surgical outcomes. This study aims to provide evidence on the safety of arthroplasty at district level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In a retrospective cohort study, Laubscher et al recently compared the results of arthroplasty procedures performed at a district and at a tertiary academic hospital, respectively [ 21 ]. Our results are in agreement with these authors who concluded that arthroplasty at district health care level is safe and may reduce the pressure on arthroplasty services at tertiary care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, Laubscher et al recently compared the results of arthroplasty procedures performed at a district and at a tertiary academic hospital, respectively [ 21 ]. Our results are in agreement with these authors who concluded that arthroplasty at district health care level is safe and may reduce the pressure on arthroplasty services at tertiary care facilities.…”
Section: Discussionmentioning
confidence: 99%